1974
DOI: 10.1097/00000658-197408000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Elective Total Gastrectomy for Cancer of the Stomach

Abstract: There has been no apparent improvement in overall salvage of patients with cancer of the stomach treated by elective extended total gastrectomy from 1950-1964 as compared with those treated by partial gastrectomy during the preceding 20-year period, 1931-1950 at Memorial Hospital in New York City. Criteria of resectability have been extended in recent years, and, therefore, the two series of patients cannot be considered strictly comparable. In the 94 patients subjected to elective total gastrectomy for cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(25 citation statements)
references
References 4 publications
2
23
0
Order By: Relevance
“…65% of which were treated with SGR, was comparable to that reported by other authors with more radical surgical procedures [6,8,11,12,15].…”
Section: Discussionsupporting
confidence: 86%
“…65% of which were treated with SGR, was comparable to that reported by other authors with more radical surgical procedures [6,8,11,12,15].…”
Section: Discussionsupporting
confidence: 86%
“…There is still controversy over the impact of the extent of resection for tumors located in the upper third of the stomach (including cardia and fundus) [21] . Some researchers [22][23][24][25] advocate the performance of PSG so as to possibly retain the stomach even partially, and proper digestive function. It also enables patients to avoid the late stage complications following TG.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports 3-year survival rates of 7-12.6% [16,19]. Regardless of the number of metastatic sites, we had a 7.03% 5-year survival rate in patients with palliative resection.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, we do not consider old age to be a contraindication to surgery. Other reports have stated that palliative resections are not associated with an increased postoperative mortality rate [16][17][18], although Hartgrink et al [7] did not recommend palliative resection for patients more than 70 years of age. They reported that when morbidity, hospital stay, and mortality are considered, no benefit exists for patients over the age of 70 undergoing palliative resection.…”
Section: Discussionmentioning
confidence: 99%